Electromagnetic transients in transformer and rotating machine windings - Su, Qi (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book explores relevant theoretical frameworks, the latest empirical research findings, and industry-approved techniques in this field of electromagnetic transient phenomena"--Provided by publisher.
Keywords: Electromagnetic waves -- Transmission.; Electromagnetic waves -- Research.; elektronické knihy; electronic books